(untitled) (European Journal of Education, 2019)
This study treats the importance of the education and the civil formation of the youth. The real possibilities that they have in expressing their free opinion and their active participation in civil actions. Relating to the experience of other countries and our country in this direction the results and possibilities for interventions need to be indicated. The goal of the study is to evaluate what is the level of the free expression of the opinion, what prevents the youth to express their opinion freely, how much support do they receive from other citizens in order to solve their problems, to assess how the university curricula help them in education and equipping them with active citizenship, if they believe that situation of the future will change and the areas and possibilities created for active participation in society. The study included 258 university students (Bachelor and Master Programs) of the Education Faculty in the university “Aleksander Moisiu” Durres. The students filled in a questionnaire with 21 closed questions. The study evaluated the problems that the students encountered, their possibilities to freely express their opinion and the factors that prevented them to do so. The study indicated that the free expression of the opinions and the active participation of the students is not in satisfactory levels. These levels are not enough for the actual requirements, and for this is required an open mind, collaboration, and funds to enhance the active citizenship. We need to accept the reality as it really is with the belief that it belongs to the present, and we should try to change the future in order to increase the youth trust in this direction.